2003
DOI: 10.1046/j.1523-1747.2003.12006.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Epidermis and Stratum Corneum of Hairless Mice with Experimentally Induced Diabetes Mellitus

Abstract: Diabetes mellitus induces many pathophysiologic changes in the skin. Even so, dermatologists still lack an animal model of diabetes that enables the direct evaluation of the various functional properties of the skin. Our group induced two types of an experimental type 1 diabetes model in hairless mice by administering either streptozotocin or alloxan, in order to examine the properties of the stratum corneum and epidermis of these animals. The plasma glucose concentrations of the mice at 3 wk after their i.v. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 53 publications
(52 reference statements)
8
80
2
Order By: Relevance
“…Contradicting results were also obtained in the studies of epidermis thickness in the case of diabetes [57]. In some papers the authors conclude that the epidermis thickness does not change [170,172,173] under the conditions of long-term hyperglycemia in rats and the diabetes mellitus in humans and mice, however, other authors using other model of diabetes mellitus or animals of other age state that the thickness either decreases [171,172,174], or increases [175]. The ultrasonic measurement of skin thickness in patients with diabetes mellitus revealed the skin thickness increase [176].…”
Section: Skinmentioning
confidence: 88%
See 2 more Smart Citations
“…Contradicting results were also obtained in the studies of epidermis thickness in the case of diabetes [57]. In some papers the authors conclude that the epidermis thickness does not change [170,172,173] under the conditions of long-term hyperglycemia in rats and the diabetes mellitus in humans and mice, however, other authors using other model of diabetes mellitus or animals of other age state that the thickness either decreases [171,172,174], or increases [175]. The ultrasonic measurement of skin thickness in patients with diabetes mellitus revealed the skin thickness increase [176].…”
Section: Skinmentioning
confidence: 88%
“…However, in Refs. [169,171] it was stated that in the case of diabetes mellitus the transepidermal loss of water does not increase. The authors of Ref.…”
Section: Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoblot Analysis-As described previously (30), the epidermis was homogenized in a lysis buffer (0.1 M Tris hydroxymethyl aminomethan-HCl (pH 9.0), 8 M urea, 1% 2-mercaptoethanol, 1% SDS, 1 mM EDTA, and 0.1 mM phenylmethylsulfonyl fluoride) and centrifuged (15,000 ϫ g for 15 min). The supernatant was used for immunoblotting.…”
Section: Generation Of Nectin-1mentioning
confidence: 99%
“…Sakai et al reported that the SC hydration and the activity of sebaceous glands decreased obviously in diabetics (Sakai et al, 2005). There were also studies that indicated hyperglycemia and decreased insulin signal were involved in the impairment of skin function (Sakai et al, 2003;Seirafi et al, 2008). In the presence of high glucose (20 mmol/l), the keratinocytes was larger, flattened and had lost some of their orientation toward each other, and the keratinocytes proliferation was decreased.…”
Section: Introductionmentioning
confidence: 99%